Synthesis, Charecterization and Nuclease Activity of Au(III)- Complexes of Biacetyl Monoxime Thiosemicarbazone(BAMOT) and Substituted Thiosemicarbazones. - Adharvanachary, M (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACT Metal complexes of Au(III) with Thiosemicarbazone and Substituted Thiosemicarbazones of different thiosemicarbazones have been synthesized. The present communication reports the structural study of the Au(III) complexes with Biacetyl Monoxime Thiosemicarbazones and these complexes have been characterised by elemental analysis, conductance, IR, NMR and Mass spectral data. The physico chemical and spectral data suggests tetrahedrol geometry for various complexes. Metal complexes of Biacetyimonoxtme thiosernicarbazone (BAMOT) and Substituted Thiosemicarbazones are also investigated for better comparison. Au(III) complexes of Biacetyimonoxtme thiosernicarbazone (BAMOT) . The ligand and metal chelates would be screened in-vitro for anticancer activity against some cancer Cell lines.